PENAMPILAN PRODUKSI TERNAK BABI GROWER SAMPAI FINISHER YANG MENGGUNAKAN TEPUNG LIMBAH IKAN CAKALANG SEBAGAI PENGGANTI SEBAGIAN KONSENTRAT DALAM RANSUM - Saud, Rifal H.; Rawung, Vonny R.W.; Soputan, Jeanette M.; Lapian, Mien Th.R. (ZOOTEC, 2019)
PRODUCTION PERFORMANCE OF GROWING PIGS FED RATION CONTAINING CAKALANG FISH WASTE PRODUCT. The study aims to determine the extent of the effect of using fish waste flour as a partial substitute for concentrates in feed on the appearance of grower phase pig production to finiser. Swines are very potential to be developed in North Sulawesi because they have the attributes and capabilities of fast growth rates, high number of litter size, good ration efficiency, and a high percentage of carcass. Cakalang fish waste is one of the feed ingredients that are potentially used as animal feed ingredients because it is easy to be obtained and its price is relatively cheap. Â Cakalang fish waste can be processed into fish meal and can be used for animal feed mixtures including swines, poultry and fishery. This research was carried out on the farm belongs to Mr. Cloudio Lumowa, starting with the pre-trial for the 2 weeks and data collection for the 10 weeks, starting on June 14 to August 26, 2017. Research was using 20 heads of gilt and boar with a range body weight of 53-63kg. The research design used was Randomized Block Design (RCBD) involving 4 treatments and 5 replications at each treatment. The treatments of feeding were including R0 = ration without cakalang fish waste flour, R1 = ration + 2% cakalang fish waste flour, R2 = ration + 4% cakalang fish waste flour, and R3 = ration + 6% cakalang fish waste flour. The results of the research showed that the use of cakalang fish waste flour with a level of 2%, 4%, and 6% had a significant effect (P< 0.05) on swine weight gain and feed effciciency, but did not affect significantly feed consumption. Based on the results of the study and discussion of all variables, it can be concluded that the use of cakalang fish waste flour as a partial replacement of concentrate up to 6% in grower to finisher produced the same ration consumption, a good body weight gain and feed efficiency.Keywords: cakalang fish waste, production, grower